2016
DOI: 10.1016/j.adolescence.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood income inequality, social capital and emotional distress among adolescents: A population‐based study

Abstract: Theory holds that income inequality may harm adolescent mental health by reducing social capital within neighborhood communities. However, research on this topic has been very limited. We use multilevel data on 102 public schools and 5958 adolescents in Iceland (15 and 16 years old) to examine whether income inequality within neighborhoods is associated with emotional distress in adolescents. Moreover, we test whether indicators of social capital, including social trust and embeddedness in neighborhood social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 92 publications
2
48
0
Order By: Relevance
“…Of the four studies in adolescents only, three found a significant association between income inequality and depression (two in the regression 23,26 and one in bivariate analysis only 28 ). Of the five studies in older adults only, three found an association between income inequality and depression (two in regression 19,22 and one in bivariate analysis only 27 ), one found no association 30 , and one found a negative association 35 .…”
Section: Associations Between Income Inequality and Depressionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the four studies in adolescents only, three found a significant association between income inequality and depression (two in the regression 23,26 and one in bivariate analysis only 28 ). Of the five studies in older adults only, three found an association between income inequality and depression (two in regression 19,22 and one in bivariate analysis only 27 ), one found no association 30 , and one found a negative association 35 .…”
Section: Associations Between Income Inequality and Depressionmentioning
confidence: 99%
“…In a similar vein, Walker et al 38 hypothesized feelings of withdrawal and shame experienced by those in lower social positions. The second neighbourhood mechanism is the social capital hypothesis, which argues that income inequality erodes social capital, including two key components: cognitive social capital (especially social trust) 26 and structural social capital (the organizational and structural arrangements which facilitate social interactions and build social trust and cooperation, for example through group membership) 39 . Figure 2 Forest plot of the association between income inequality and depression.…”
Section: Scoping Review Of Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are even studies finding no linkage between income inequality and environmental quality [45,46]. Some studies found that income anticipations could affect mental health and that income inequality generally damaged subjective well-being and led to psychological problems [18,[47][48][49][50][51]. Further, Velek and Steg (2007) proposed that psychological factors were important in promoting sustainable consumption of natural resources [52].…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic inequalities in health and mental health may form along several pathways [4]. One is social participation (SP), which is broadly defined as the individual's involvement in activities that include interactions with others in the society [5] and embraces various practices of informal and formal social connections and activities [6].…”
Section: Introductionmentioning
confidence: 99%